Biomass‐based Hierarchical Porous Carbon for Supercapacitors: Effect of Aqueous and Organic Electrolytes on the Electrochemical Performance. Issue 23 (28th October 2019) - Chen, Zhimin; Wang, Xiaofeng; Ding, Zhiyao; Wei, Qingling; Wang, Zichen; Yang, Xiaomin; Qiu, Jieshan
Abstract: Biomass‐based hierarchical porous carbon (SCPC) exhibits excellent electrochemical performance in electric double layer capacitors, prepared by carbonization and activation of straw cellulose. To investigate the potential applications of SCPC in supercapacitors, the effect of aqueous and organic electrolytes on the electrochemical performance of SCPC was studied in detail. In H2 SO4, the SCPC electrode exhibits higher specific capacitance (358 F g −1 ) and outstanding cycling stability with 95.6 % capacitance retention over 10 000 cycles. The SCPC electrode shows superior rate capability with 90.7 % capacitance retention in KOH, and higher energy density of 17.9 Wh kg −1 in Na2 SO4 . The SCPC electrode exhibits ideal capacitance characteristics, superior rate capability with capacitance retention of 95.8 %, and high energy density of 36.0 Wh kg −1 in tetraethylammonium tetrafluoroborate/propylene carbonate (Et4 NBF4 /PC). The significant difference of capacitive performance of SCPC electrode in various electrolytes is mainly attributed to the difference in the electrolyte ion size, ionic conductivity, matching between the electrolyte ions and pore structure, and matching between anions and cations adsorbed on the positive and negative electrodes. This work not only establishes the relationship between the structure of SCPC and its electrochemical performance in different electrolytes, but also provides a reference for the high value‐added utilization of SCPC. Abstract : Electrolyte cap‐atibility : Biomass‐based hierarchical porous carbon (SCPC) is shown to exhibit excellent electrochemical performance in an electric double‐layer capacitor. The effect of aqueous and organic electrolytes on the electrochemical performance of SCPC is studied, providing a valuable reference for the potential applications of SCPC in supercapacitors with different electrolytes. The relationship between the structure of SCPC and its electrochemical performance in different electrolytes is also established.